The Impact of Parental Screen Time Implementation on Cognitive Development in Early Childhood - Fania Mersieni; Choiriyah, Choiriyah; Chandra Apriyansyah (Bulletin of Early Childhood, 2025)
This study aims to analyze the impact of parental implementation of screen time on the cognitive development of early childhood children at TKIT Al Ikhlas 86 Bekasi. The focus includes the daily duration of screen use, the role of parental supervision, and the application patterns of screen time rules, related to cognitive aspects such as thinking ability, concentration, language, and memory. A qualitative approach was used through observation, interviews, and documentation, involving parents and early childhood children at the school. Data were analyzed descriptively to gain an in-depth understanding of screen time practices and their effects on children’s cognitive development. The results indicate that screen time has a dual impact; when used with limited duration, educational content, and active parental involvement, it can stimulate positive outcomes such as increased vocabulary, problem-solving skills, and creativity. Conversely, excessive use without supervision may reduce concentration, hinder language development, and decrease social interaction. Therefore, parental roles in managing screen time are crucial, with consistent rules enforcement, quality content selection, and active engagement as key strategies to maximize benefits and minimize negative effects. These findings are expected to serve as practical references for parents, educators, and policymakers in supporting early childhood cognitive development in the digital era.